2009
DOI: 10.1902/jop.2009.090214
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy May Promote Periodontal Healing Through Multiple Mechanisms

Abstract: aPDT treatment may augment periodontal treatment by increasing bacterial killing, inactivating bacterial virulence factors, and inactivating host cytokines that impair periodontal restoration. Therefore, aPDT treatment may provide a more favorable healing environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 47 publications
3
70
0
6
Order By: Relevance
“…In other observations of PDT application, there was a remarkable reduction of lymphocytes in the irradiated tissues [51]. An inactivation of host destructive cytokines, which prevent periodontal tissue regeneration, is also an important outcome of this therapy [52]. In terms of antibacterial properties, it has been confirmed that topically applied toluidine blue and laser light are able to kill P.gingivalis from the gingival crevice without any damage of the adjacent tissues.…”
Section: Application Of Pdt In Periodontal Therapymentioning
confidence: 86%
“…In other observations of PDT application, there was a remarkable reduction of lymphocytes in the irradiated tissues [51]. An inactivation of host destructive cytokines, which prevent periodontal tissue regeneration, is also an important outcome of this therapy [52]. In terms of antibacterial properties, it has been confirmed that topically applied toluidine blue and laser light are able to kill P.gingivalis from the gingival crevice without any damage of the adjacent tissues.…”
Section: Application Of Pdt In Periodontal Therapymentioning
confidence: 86%
“…25 A plausible explanation for this improvement in the SRP + aPDT group patients could be bacterial load reduction and inactivation of bacterial virulence factors and cytokines when the photosensitizer dye is irradiated with laser. 26 Komerik et al successfully demonstrated killing of Porphyromonas gingivalis in the gingival crevices of rats without damaging the adjacent periodontal tissues. 27 In another study, Pinheiro et al showed a significantly greater reduction in the percentage of viable bacteria in periodontal pockets treated with aPDT (96%) compared to those treated with SRP alone (81%).…”
Section: Discussionmentioning
confidence: 99%
“…A single antimicrobial PDT treatment in vitro potently inactivated protease activity and resulted in a 4 log 10 reduction in the viability of P. gingivalis. 139 Dose and time-of-exposure experiments revealed that protease inactivation occurred at lower concentrations of PS and less time of light exposure. Also, antimicrobial PDT treatment has been shown to be potently and functionally inactivated IL-1β and TNFα.…”
Section: Biofilm Eradicationmentioning
confidence: 98%
“…Also, antimicrobial PDT treatment has been shown to be potently and functionally inactivated IL-1β and TNFα. 139 …”
Section: Biofilm Eradicationmentioning
confidence: 99%